Feasibility and challenges of Tik-Tok's integration into value education/ Rui Liu& Izaham Shah Ismail - Liu, Rui; Ismail, Izaham Shah (2023)
Tik-Tok has become an important tool in the life of Chinese college students with the characteristics of "video + music + social networking"; it has influence on their values. The main body and object of university value education work are college students. Paying attention to the new characteristics and changes in the ideological behavior of college students and using new media to innovate educational methods are new requirements for doing an important job in university value education. This paper analyzed the driving factors of Tik-Tok’s popularity among college students in China, investigated the inner connection between Tik-Tok and Chinese college students' value education, analyzed the possibility and challenges of Tik-Tok's integration into the value education of Chinese college students, and put countermeasures.